Alkali metal-resistant mechanism for selective catalytic reduction of nitric oxide over V2O5/HWO catalysts. (15th November 2021) - Kang, Running; He, Junyao; Bin, Feng; Dou, Baojuan; Hao, Qinglan; Wei, Xiaolin; Nam Hui, Kwun; San Hui, Kwan
Graphical abstract: Highlights: The controllable morphology synthesis of hexagonal WO3 (HWO) was achieved by commercial bacterial cellulose (C). The obtained V2 O5 /HWO-C catalyst exhibits effective resistance to K poisoning and SO2, and follows the Langmuir-Hinshelwood mechanism. The detailed alkali metal-resistant pathways for the distribution of alkali metal ions (K + ) on the K-V2 O5 /HWO-C catalyst were proposed. Abstract: A series of V2 O5 /HWO catalysts are prepared by hydrothermal and impregnation methods using different precursors, among which the V2 O5 /HWO-C catalyst exhibited the optimal NH3 -SCR performance. Compared to oxalic acid (O) and water (W), commercial bacterial cellulose (C) as a precursor can firstly achieve a more controllable synthesis to form hexagonal WO3 (HWO) of V2 O5 /HWO-C catalyst. Various characterization (XRD, N2 -BET, TEM, SEM, XPS, EDX mapping, and NH3 /NO-TPD-MS) indicate that a higher specific surface area, abundant active oxygen and surface acidity result from the V2 O5 /HWO-C catalyst. The reason is that HWO-C has an excellent and smooth rod-shaped morphology, which promotes high dispersion of V2 O5 on its surface. In situ IR results show that the SCR follows the Langmuir-Hinshelwood (L-H) mechanism, where absorbed NOx intermediate species are formed on the V2 O5 and react with the NH4 + and NH3abs groups of V2 O5 and HWO. After loading 1.75 wt% K +, the obtained K-V2 O5 /HWO-C catalyst exhibits effective resistance to K poisoning and SO2, and retains 78 % NOx conversion efficiency at 360 °C after 10 h, attributed to the effective capture of K + (1.04 wt%) in HWO-C channels via a new pathway, although approximately 0.71 wt% K + are located on HWO-C external surface with weak bonding to V2 O5 .